2017
DOI: 10.3389/fnhum.2017.00360
|View full text |Cite
|
Sign up to set email alerts
|

Performance Monitoring Applied to System Supervision

Abstract: Nowadays, automation is present in every aspect of our daily life and has some benefits. Nonetheless, empirical data suggest that traditional automation has many negative performance and safety consequences as it changed task performers into task supervisors. In this context, we propose to use recent insights into the anatomical and neurophysiological substrates of action monitoring in humans, to help further characterize performance monitoring during system supervision. Error monitoring is critical for humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 116 publications
(238 reference statements)
0
6
0
1
Order By: Relevance
“…Besides the suggested overlap between the neural systems responding to observed and executed actions and errors (Zubarev et al, 2018) studies have documented a differential contribution of brain areas to the observation of errors performed by others (Shane et al, 2008;Abreu et al, 2012;Somon et al, 2019;Ninomiya, et al, 2018;Somon et al, 2017). In the present study we explored the neural responses associated to coordinating one's own movements with those of a virtual partner who could perform unexpected changes in its motor behaviour.…”
Section: Action and Error Monitoring During Motor Interactionsmentioning
confidence: 98%
“…Besides the suggested overlap between the neural systems responding to observed and executed actions and errors (Zubarev et al, 2018) studies have documented a differential contribution of brain areas to the observation of errors performed by others (Shane et al, 2008;Abreu et al, 2012;Somon et al, 2019;Ninomiya, et al, 2018;Somon et al, 2017). In the present study we explored the neural responses associated to coordinating one's own movements with those of a virtual partner who could perform unexpected changes in its motor behaviour.…”
Section: Action and Error Monitoring During Motor Interactionsmentioning
confidence: 98%
“…Previous research has examined neural correlates of trust between people ( Adolphs, 2002 ; Delgado et al, 2005 ; King-Casas et al, 2005 ; Krueger et al, 2007 ) and while it is expected that the overall trust process for people and automation is similar, it is likely that important and specific differences will emerge between people and machines ( Madhavan and Wiegmann, 2007b ; de Visser et al, 2016 ). While contributions toward understanding trust in automated systems from a neuroscientific viewpoint are still limited, recent reviews have pointed to the potential of applying known neural correlates of performance monitoring to the monitoring of machines ( Fedota and Parasuraman, 2010 ; Drnec et al, 2016 ; Berberian et al, 2017 ; Somon et al, 2017 ). Consistent with this idea, a recent study found that false alarm-prone advice activated different brain regions for a human compared to a machine, including the precuneus, posterior cingulate cortex, and temporoparietal junction ( Goodyear et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For reviews on performance monitoring components and their applications seeGehring et al (2011) orSomon et al (2017).…”
mentioning
confidence: 99%